Pengaruh Literasi Keuangan dan Inklusi Keuangan Terhadap Perilaku Keuangan Generasi-Z di Universitas Muhammadiyah Surakarta dengan Financial Self-Efficacy sebagai Variabel Intervening - Ayu T P, Delonika Diah; Imronudin, Imronudin (Universitas Pakuan, 2025)
THE EFFECT OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON THE FINANCIAL BEHAVIOR OF GENERATION-Z AT THE UNIVERSITY OF MUHAMMADIYAH SURAKARTA WITH FINANCIAL SELF-EFFICACYThis study aims to thoroughly examine the influence of financial literacy and financial inclusion on the financial attitudes of Generation Z students at Universitas Muhammadiyah Surakarta, with financial self-efficacy acting as an intervening variable. A quantitative research approach was employed by distributing questionnaires to 101 respondents, and the collected data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). This analytical method enabled the researcher to assess both direct and indirect relationships among the variables comprehensively. The findings reveal that financial literacy has a positive and significant effect on financial self-efficacy as well as on financial attitudes. Moreover, financial literacy exerts a significant indirect influence on financial attitudes through financial self-efficacy, indicating that confidence in managing finances serves as an essential mechanism that strengthens the role of financial knowledge in shaping responsible financial behavior. Meanwhile, financial inclusion demonstrates a positive and significant impact on financial attitudes but does not significantly affect financial self-efficacy. Therefore, financial self-efficacy does not mediate the relationship between financial inclusion and financial attitudes. Overall, the results emphasize the importance of improving financial literacy and enhancing financial self-efficacy to foster wiser and more responsible financial behaviors among Generation Z students. Continuous financial education and broader access to financial services are crucial to support students in making informed and accountable financial decisions.